Major fertilization sources and mechanisms for Mediterranean Sea coastal ecosystems. (6th October 2017) - Macias, D.; Garcia‐Gorriz, E.; Stips, A.
Abstract: The Mediterranean Sea is considered an oligotrophic basin with a few biological production hotspots. Some of these productive regions are under the influence of large rivers' discharges and have been described to suffer from eutrophication indications. In order to quantify the impact of the river‐borne inorganic nutrients on the pelagic production levels and bottom oxygen conditions in the northern coast of the Mediterranean Sea, two hindcast simulations using a coupled hydrodynamic‐biogeochemical model are compared. Both simulations cover a 60 yr period and are identical except for the rivers' conditions, one is performed considering realistic inorganic nutrient levels in the rivers' waters while the second has no inorganic nutrients coming from the freshwater discharges. Comparing these two simulations we found that inorganic nutrients in the rivers are responsible for a large fraction of the pelagic primary production and for the totality of bottom hypoxic zones in both the Adriatic and Aegean basin. On the contrary, river fertilization is of marginal importance for the coastal ecosystem of the NW Mediterranean Sea, where mesoscale processes and associated vertical transport of nutrients are the main processes responsible for the majority of the production. We, finally, discuss the consequences of these fundamental differences in fertilization for freshwater management and ecosystems status evaluation in the light of different policy options and within the context of future climate change.